2020
DOI: 10.1590/1519-6984.211956
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal helminths in dog feces surrounding suburban areas of Lower Dir district, Pakistan: A public health threat

Abstract: Data on environmental contamination of the parasites of zoonotic importance is scarce in Pakistan. Soil contamination with feces of dogs hide infective stages of the parasite represents a health-risk to humans. This study was aimed to assess the eggs of gastrointestinal parasites of stray dogs and household dogs in lower Dir district, Pakistan with special consideration to those that can be spread to humans. One hundred and fifty two stool specimens from (stray dogs=90 and household dogs=62) were collected. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
5
7
1
2
Order By: Relevance
“…Co-infection with hookworms and D. caninum was most common. In comparison to this study, more dogs in Canada, Hungary and Pakistan were found to have co-infections with two helminth species, while in Tanzania and Australia co-infections were less common ( Khan et al., 2020 ). Finally, no trematode species were detected, while in Nam Dinh Province 56.9% of dogs were found infected with fish-borne trematodes, including Clonorchis sinensis and minute intestinal flukes ( Nguyen et al., 2009 ).…”
Section: Resultscontrasting
confidence: 95%
“…Co-infection with hookworms and D. caninum was most common. In comparison to this study, more dogs in Canada, Hungary and Pakistan were found to have co-infections with two helminth species, while in Tanzania and Australia co-infections were less common ( Khan et al., 2020 ). Finally, no trematode species were detected, while in Nam Dinh Province 56.9% of dogs were found infected with fish-borne trematodes, including Clonorchis sinensis and minute intestinal flukes ( Nguyen et al., 2009 ).…”
Section: Resultscontrasting
confidence: 95%
“…Sixteen out of 108 (14.81%) fecal samples were found infected with D. caninum in different areas of Baghdad city (Table 1). The highest infection rate was 20.37% (11/54) found in stray dogs, while the lowest was 9.26% (5/54) in pet dogs, with a significant difference (P<0.01) Our estimation of D. caninum infection was similar to recorded 14.8% (59/400) from Nigeria (13), also 18.7% SALIH DA AND ABASS AK (18/96) in Nigeria (20), and 11.8% (18/152) in Pakistan (21). While the study's results were lower than the one in Palestine, which was 23% (35/150) ( 14) which was higher than the 1% (1/77) reported in Iran (22).…”
Section: Resultssupporting
confidence: 84%
“…Around the world, there are some reports of gastrointestinal parasitism in dogs, and the frequencies of the parasites detected were 26.5% (80/302) in Villahermosa, Mexico (Torres-ChablĂ© et al, 2015); 40% (120/300) in Central Queensland, Australia (Gillespie & Bradbury, 2017); 26.8% (41/152) on the Lower Dir district, Pakistan (Khan et al, 2020); 63.5% (148/233) in northern Spain (Regidor-Cerrillo et al, 2020); and 11.9% (43/360) on the Shendi area, Sudan (Sulieman et al, 2020). Likewise, different occurrences are reported in Brazil, 20.5% (635/3099) in SĂŁo Paulo (Ferreira et al, 2016); 43.2% (147/340) on the northeastern region (Zanetti et al, 2019); 72.55% (74/102) in Caxias do Sul (Lusa et al, 2021); and 87.5% (35/40) in Porto Velho (Lopes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%